2014
DOI: 10.1186/1476-7120-12-31
|View full text |Cite
|
Sign up to set email alerts
|

Elevated level of plasma endothelin-1 in patients with atrial septal defect

Abstract: BackgroundThe study aimed to assess the level of plasma Endothelin-1 (ET-1) in patients before and after transcatheter closure of atrial septal defect (ASD) and to evaluate the usefulness of measuring ET-1 levels for the diagnosis and selection of candidates for ASD closure.Methods80 patients (55 F, 25 M), mean age 42,2 ± 11,5 years were enrolled for an attempt at ASD closure. A group of 19 healthy volunteers, (12 F, 7 M) mean age 39.2 ± 9.15 served as controls. All ASD patients underwent: clinical and echocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…Li et al [12] reported a similar result after investigating 30 healthy subjects and 58 PAH patients. Recent study comparing endothelin-1 level from 80 adults ASD and 19 healthy subjects found that endothelin-1 level was significantly higher in unclosed ASD than in that with closed defects [13]. In this study, prostacyclin level was not significantly correlated with mPAP.…”
Section: Discussioncontrasting
confidence: 65%
“…Li et al [12] reported a similar result after investigating 30 healthy subjects and 58 PAH patients. Recent study comparing endothelin-1 level from 80 adults ASD and 19 healthy subjects found that endothelin-1 level was significantly higher in unclosed ASD than in that with closed defects [13]. In this study, prostacyclin level was not significantly correlated with mPAP.…”
Section: Discussioncontrasting
confidence: 65%
“…Recently, a group showed that plasma endothelin-1 levels were associated with right heart enlargement and were reduced following percutaneous ASD closure. 29 It was suggested that endothelin-1 might be useful as a diagnostic test when evaluating patients for ASD closure; however, further studies are needed to delineate its clinical role.…”
Section: Interventionmentioning
confidence: 99%